A new approach to dengue fatal cases diagnosis: NS1 antigen capture in tissues. - Monique da Rocha Queiroz Lima; Rita Maria Ribeiro Nogueira; Hermann Gonçalves Schatzmayr; Ana Maria Bispo de Filippis; Daniel Limonta; Flavia Barreto dos Santos (Public Library of Science (PLoS), 2011)
UNLABELLED: / BACKGROUND: Dengue is the most important arthropod borne viral disease worldwide in terms of morbidity and mortality and is caused by any of the four serotypes of dengue virus (DENV-1 to 4). Brazil is responsible for approximately 80% of dengue cases in the Americas, and since the introduction of dengue in 1986, a total of 5,944,270 cases have been reported including 21,596 dengue hemorrhagic fever and 874 fatal cases. DENV can infect many cell types and cause diverse clinical and pathological effects. The goal of the study was to investigate the usefulness of NS1 capture tests as an alternative tool to detect DENV in tissue specimens from previously confirmed dengue fatal cases (n = 23) that occurred in 2002 in Brazil. METHODOLOGY/PRINCIPAL FINDINGS: A total of 74 tissue specimens were available: liver (n = 23), lung (n = 14), kidney (n = 04), brain (n = 10), heart (n = 02), skin (n = 01), spleen (n = 15), thymus (n = 03) and lymph nodes (n = 02). We evaluated three tests for NS1 antigen capture: first generation Dengue Early ELISA (PanBio Diagnostics), Platelia NS1 (BioRad Laboratories) and the rapid test NS1 Ag Strip (BioRad Laboratories). The overall dengue fatal case diagnosis based on the tissues analyzed by Dengue Early ELISA, Platelia NS1 and the NS1 Ag Strip was 34.7% (08/23), 60.8% (14/23) and 91.3% (21/23), respectively. The Dengue Early ELISA detected NS1 in 22.9% (17/74) of the specimens analyzed and the Platelia NS1 in 45.9% (34/74). The highest sensitivity (78.3%; 58/74) was achieved by the NS1 Ag Strip, and the differences in the sensitivities were statistically significant (p<0.05). The NS1 Ag Strip was the most sensitive in liver (91.3%; 21/23), lung (71.4%; 10/14), kidney (100%; 4/4), brain (80%; 8/10), spleen (66.6%, 10/15) and thymus (100%, 3/3) when compared to the other two ELISA assays. CONCLUSIONS/SIGNIFICANCE: This study shows the DENV NS1 capture assay as a rapid and valuable approach to postmortem dengue confirmation. With an increasing number of DHF and fatal cases, the availability of new approaches useful for cases confirmation plays an important tool for the disease surveillance.